2004
DOI: 10.1029/2003gl018980
|View full text |Cite
|
Sign up to set email alerts
|

Ocean bottom pressure waves predicted in the tropical Pacific

Abstract: Using a mass‐conserving (non‐Boussinesq) Pacific Ocean model and TOPEX/POSEIDON sea‐surface height measurements, we document previously unreported bottom pressure waves (BPWs), associated with large‐amplitude eddies (vortices) both north and south of the Equator. The bottom pressure signals, defined as the vertically integrated water‐mass anomalies, are found to propagate westward across the Pacific Ocean with an approximate 4‐mbar amplitude (1 mbar = 100 Newton/m2, approximately equivalent to 1 cm of sea surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…3 and 4 bear a close resemblance to fields shown in the GCM studies of Cox (1980) and Song and Zlotnicki (2004), which showed the barotropic streamfunction with similar filtering and ocean bottom pressure, respectively. Cox (1980) made clear that the variability seen at higher latitudes in his model was a result of the TIWs and that the signal was barotropic.…”
Section: B Interpretation As Barotropic Rossby Wavesmentioning
confidence: 84%
See 4 more Smart Citations
“…3 and 4 bear a close resemblance to fields shown in the GCM studies of Cox (1980) and Song and Zlotnicki (2004), which showed the barotropic streamfunction with similar filtering and ocean bottom pressure, respectively. Cox (1980) made clear that the variability seen at higher latitudes in his model was a result of the TIWs and that the signal was barotropic.…”
Section: B Interpretation As Barotropic Rossby Wavesmentioning
confidence: 84%
“…This result was presaged, remarkably, by the first general circulation model (GCM) study of TIWs (Fig. 12 of Cox 1980), and similar variability was also seen in the GCM study of Song and Zlotnicki (2004). Proehl (1996) performed a linear stability analysis for an equatorial zonal-channel model with boundaries at 108N and 108S, and he found unstable modes that included barotropic variability on 78-108N and 78-108S, near the poleward edge of the model domain (Fig.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations